Controls on runoff generation along a steep climatic gradient in the Eastern Mediterranean - Fabian Ries (Journal of Hydrology: Regional Studies, 2017)
Study region: Lower Jordan River. Study focus: The main aim of this study was to identify differences in catchment runoff reactions across a variety of scales and a strong climatic gradient and to correlate them to physical catchment properties. For this purpose we observed rainfall and runoff responses on a hillslope (1000 m2) and in several nested catchments (3.2–129 km2) over a period of five years. Catchment characteristics and surface cover types were derived from high-resolution aerial images. To gain process understanding a single high magnitude event was analysed in detail using information from soil moisture plots. New hydrological insights for the region: Our results show that runoff in the semi-arid headwater area is strongly related to long lasting rainfall events of high amounts and is predominantly generated by saturation excess overland flow (SOF). Observations from the arid runoff plot indicated a strongly contrasting behaviour with dominating Hortonian overland flow (HOF). At catchment scale we found an accentuated runoff response when we compared arid with semi-arid conditions, which can be attributed to different geological substrate, more abundant rock surfaces, shallower soil and sparser vegetation cover. Identified strong correlations between event rainfall and runoff volumes may provide promising options for the assessment and management of surface runoff as a water resource.